EFFECT OF NITROGEN AND BIOFERTILIZATION, SEAWEED EXTRACT AND THIAMINE ON GROWTH, YIELD AND ESSENTIAL OIL OF PARSLEY PLANT - M. Aly; E.T. Ahmed; M. Mohamed; El-Zahraa Youssef (Scientific Journal of Flowers and Ornamental Plants, 2021)
A field experiment was carried out to study the effect of reducing the recommended dose of mineral N fertilizer on parsley (Petroselinum sativum, Hoffm.) plants. To achieve this aim, some bio-stimulants commercial product (Minia azotein) which contain N fixing bacteria, seaweeds extract at 100 and 200 ppm and thiamine (Vit. B1) at 100 and 200 ppm, separately or in combinations were used. Results revealed that mineral N at 50 to 75% + Minia azotein significantly stimulated the vegetative growth traits, yield components, essential oil content, photosynthetic pigments and N % relatively to control plants (recommended dose of mineral N). Using mineral N fertilizer at 25% and Minia azotein significantly reduced the above-mentioned characters compared to check treatment. All treatments of seaweeds extract and/or thiamine (Vit. B1) significantly augmented the vegetative growth parameters, yield components, essential oil photosynthetic pigments and N % compared with control plants. The most effective treatment was seaweeds extract and Vit. B1 both at 200 ppm. The best results with regard to the herb dry and, fruit weight and essential oil productivity were obtained as a result of using N fertilizer at 50% plus Minia azotein in combinations with seaweeds extract + Vit. B1 each at 200 ppm